Gêneros discursivos e autoria : a produção escrita na escola - Ribeiro, Josilene Auxiliadora (2013)
On this research, we reflected on the necessity and relevance of learning-teaching of Portuguese by means of speech genre, where all grammatical aspects materialize, besides those essentially discursive ones. Departing from the hypothesis that if the student is exposed to a systematic and systematized work of reading and writing of different genres, he'll learn to dominate the discursive-linguistic resources required to authoral writing production, we elaborated a didactic sequence and achieved, during seven months, reading classes, contents discussion, identification of the characteristics of the discursive genre 'reader's letter' - compositional form, thematic style and contents - and analysis of issues published in national magazines directed to different audiences. During this period of studies, five productions of reader's letters were proposed, so that students could manifest themselves about the contents of five articles read and discussed in classroom. According to the needs of each student, letters' rewritings were asked. From this process, we selected the productions from three girl students and we analysed the authorship marks identifiable in the concrete enunciations produced by them, considering the context of interaction required for the student-author building. Our reflexions and analyses are anchored on the enunciative- discursive theory, of a socio-historical approach from Bakhtin's circle, just like on Vigotski's teaching-learning theory, author who argues about the necessity of the contextualized teaching of grammar. On our analysis, we made clear the theoretical presuppositions of Vigotski and his Circle on the building of a living, real language, such as: interaction, concrete enunciation, dialogism, active responsive comprehension, aesthetic activity, alterity and exotopia. That way, we concluded to be possible the teaching of Portuguese language by means of speech genres, which allow the student to position himself before the speeches that circulate on the several spheres of human activity.